2001
DOI: 10.1002/1097-0142(20010615)91:12<2222::aid-cncr1252>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Methylation ofp15 andp16 genes in adult acute leukemia

Abstract: Providing a context for learning information and requiring learners to teach specific content has been demonstrated to enhance knowledge retention. To enhance students' appreciation of the role of science and specifically histology in clinical reasoning, disease diagnosis, and treatment, a new teaching format was created to provide clinical context, promote integration and application of science knowledge, and to foster peer teaching and learning: the Clinico‐Histologic Conference (CHC) for the Mount Sinai Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Only a few studies to date have attempted to correlate p15 INK4B promoter methylation with clinical outcome. In ALL, no correlation between p15 INK4B promoter methylation with outcome (Chim et al, 2001b) or disease progression (Batova et al, 1997) was found. An inverse correlation between p15 INK4B methylation and overall survival was reported in adult AML (Wong et al, 2000).…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…Only a few studies to date have attempted to correlate p15 INK4B promoter methylation with clinical outcome. In ALL, no correlation between p15 INK4B promoter methylation with outcome (Chim et al, 2001b) or disease progression (Batova et al, 1997) was found. An inverse correlation between p15 INK4B methylation and overall survival was reported in adult AML (Wong et al, 2000).…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…In contrast, there is considerable data to show that inactivation of tumor suppressor genes by DNA methylation plays important roles in the pathogenesis and prognostification of hematological malignancies (Chim et al, 2001a,b, 2003b, 2004a,b, 2005a,b). For instance, methylation of retinoic acid receptor alpha (RARA), PTPN6, and DAPK genes has been implicated in pathogenesis of AML, myeloma, and CLL respectively (Reik and Walter, 2001; Chim et al, 2002, 2006; Kaneda et al, 2004).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%